Integrating depth-dependent protist dynamics and microbial interactions in spring succession of a freshwater reservoir - Indranil Mukherjee; Vesna Grujčić; Michaela M. Salcher; Petr Znachor; Jaromír Seďa; Miloslav Devetter; Pavel Rychtecký; Karel Šimek; Tanja Shabarova (Environmental Microbiome, 2024)
Abstract Background Protists are essential contributors to eukaryotic diversity and exert profound influence on carbon fluxes and energy transfer in freshwaters. Despite their significance, there is a notable gap in research on protistan dynamics, particularly in the deeper strata of temperate lakes. This study aimed to address this gap by integrating protists into the well-described spring dynamics of Římov reservoir, Czech Republic. Over a 2-month period covering transition from mixing to established stratification, we collected water samples from three reservoir depths (0.5, 10 and 30 m) with a frequency of up to three times per week. Microbial eukaryotic and prokaryotic communities were analysed using SSU rRNA gene amplicon sequencing and dominant protistan groups were enumerated by Catalysed Reporter Deposition-Fluorescence in situ Hybridization (CARD-FISH). Additionally, we collected samples for water chemistry, phyto- and zooplankton composition analyses. Results Following the rapid changes in environmental and biotic parameters during spring, protistan and bacterial communities displayed swift transitions from a homogeneous community to distinct strata-specific communities. A prevalence of auto- and mixotrophic protists dominated by cryptophytes was associated with spring algal bloom-specialized bacteria in the epilimnion. In contrast, the meta- and hypolimnion showcased a development of a protist community dominated by putative parasitic Perkinsozoa, detritus or particle-associated ciliates, cercozoans, telonemids and excavate protists (Kinetoplastida), co-occurring with bacteria associated with lake snow. Conclusions Our high-resolution sampling matching the typical doubling time of microbes along with the combined microscopic and molecular approach and inclusion of all main components of the microbial food web allowed us to unveil depth-specific populations’ successions and interactions in a deep lentic ecosystem.